2021
DOI: 10.3389/fvets.2021.656902
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamics and Pharmacokinetics of Injectable Pimobendan and Its Metabolite, O-Desmethyl-Pimobendan, in Healthy Dogs

Abstract: Objectives: This study was designed to thoroughly evaluate the effects of bolus pimobendan at a dose of 0.15 mg/kg on cardiac functions, hemodynamics, and electrocardiographic parameters together with the pharmacokinetic profile of pimobendan and its active metabolite, o-desmethyl-pimobendan (ODMP), in anesthetized dogs.Methods: Nine beagle dogs were anesthetized and instrumented to obtain left ventricular pressures, aortic pressures, cardiac outputs, right atrial pressures, pulmonary arterial pressures, pulmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…In HF, the mitochondria are dysfunctional resulting in impaired myocardial energetics (e.g., decreased ATP content) subsequently less ATP available for muscular relaxation [ 15 ]. Several studies in dogs [ 16 18 ] have shown improvement of diastolic function by pimobendan which could be partly explained by our findings.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…In HF, the mitochondria are dysfunctional resulting in impaired myocardial energetics (e.g., decreased ATP content) subsequently less ATP available for muscular relaxation [ 15 ]. Several studies in dogs [ 16 18 ] have shown improvement of diastolic function by pimobendan which could be partly explained by our findings.…”
Section: Discussionsupporting
confidence: 70%
“…Pimobendan, a benzimidazole-pyridazinone derivative, so-called inodilator, acts by inhibiting PDE-III leading to increased concentrations of cAMP and sensitizing the cardiac contractile apparatus to intracellular calcium, producing vasodilation and positive inotropic effects that have been demonstrated in several species [ 18 , 22 – 25 ]. This study showed that pimobendan maintained cardiac contractility through the end of the experiment.…”
Section: Discussionmentioning
confidence: 99%
“…This decision was made based on studies evaluating intravenous pimobendan in healthy dogs, in which pimobendan resulted in an increased stoke volume, increased cardiac output and decreased systemic vascular resistance. 17,18 Our patient already had evidence consistent with increased stroke volume and increased cardiac output on Echo coupled with the concern for decreased systemic vascular resistance with high-output cardiac failure, thus we ultimately elected not to start pimobendan in our patient. Additional factors taken into account during the clinical decisionmaking process included the absence of data that supports pimobendan administration in patient with high-output cardiac failure and mindfulness of the financial impact on the client.…”
Section: Discussionmentioning
confidence: 99%
“…Although pimobendan therapy is part of the standard of care for treating congestive heart failure in dogs with myxomatous mitral valve disease, 15,16 this drug was not prescribed in this patient due to concern for further reduction in systemic vascular resistance due to the vasodilatory effects from inhibition of phosphodiesterase III. This decision was made based on studies evaluating intravenous pimobendan in healthy dogs, in which pimobendan resulted in an increased stoke volume, increased cardiac output and decreased systemic vascular resistance 17,18 . Our patient already had evidence consistent with increased stroke volume and increased cardiac output on Echo coupled with the concern for decreased systemic vascular resistance with high‐output cardiac failure, thus we ultimately elected not to start pimobendan in our patient.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the increase in cardiac contractility from pimobendan is similar to that provided by dobutamine but with a longer duration of effect. This fact, combined with the absence of pro-arrhythmogenic effects, makes pimobendan a beneficial drug for improving CO and achieving hemodynamic stabilisation in a sustained manner over time [ 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%